A CGE Analysis of Indonesia's Free Trade Agreements - Yutiningsari, Galuh Narulita (Jurnal Ilmiah Administrasi Publik, 2020)
Using the Global Trade Analysis Project (GTAP) CGE model of the global economy, this essay analyses how much trade agreements between Indonesia and its top three trading partners – China, Japan, and the USA – could benefit Indonesia and those trading partners. In addition, an analysis of unilateral trade liberalization in Indonesia is included to provide a comparison of alternative trade liberalization policy strategies. The study conducts experiments by simulating the potential effect of the removal tariffs on imported merchandise under each liberalization scenario. The result suggests that the impact of trade liberalization is variable between strategies, but the greatest economic benefit is from the unilateral scenario. However, the restrictiveness of preferential RoO and other regulations in bilateral agreements would limit the scope for achieving the full benefit projected for the bilateral liberalization scenarios – discount rates of around 25 percent have been suggested.